Liver Stiffness Is a Predictor of Rebleeding in Patients With Hepatitis B-Related Cirrhosis: A Real-World Cohort Study - Liu, Linxiang; Nie, Yuan; Zhang, Yue; Liu, Qi; Zhu, Xuan (Frontiers in Medicine, 2021)
Background: Esophageal vein rebleeding is a life-threatening complication of liver cirrhosis. However, the role of non-invasive methods that were developed to evaluate the severity of chronic liver disease, especially in rebleeding, remains unclear. Aims: To evaluate the performance of liver stiffness and non-invasive fibrosis scores in predicting esophageal vein rebleeding in hepatitis B virus (HBV) cirrhotic patients. Methods: A prospective analysis of 194 HBV patients between 2017 and 2021 was performed. Receiver operating characteristic (ROC) curves and time-dependent ROC curves were used to assess the power for predicting rebleeding with non-invasive fibrosis score and liver stiffness. Results: During the median follow-up time of 68.28 weeks, 55 patients experienced rebleeding. In the entire cohort, the area under the ROC curve for liver stiffness measurement (LSM) predicting for rebleeding was 0.837, with a cut-off value of 17.79 kPa, and the time-dependent ROC curve also showed stable prediction performance of LSM. The predictive ability of the non-invasive fibrosis score was less than that of LSM, and there were statistical differences. Moreover, patients using non-selective beta-blockers and HBV DNA-negative patients experienced significantly reduced rebleeding. Conclusions: Compared with non-invasive fibrosis scores, LSM can more simply and accurately predict rebleeding events of hepatitis B liver cirrhosis.